Outcome Assessment of the Endoscopic Surgery for Laryngeal Trauma Management - Chung Tran, Thuy Phan (International Journal of Innovative Research in Medical Science, 2017)
Background: Laryngeal trauma which could be lead to death or laryngeal stenosis if not being discovered and treated is one of the important emergencies in otolaryngology. Methods: Prospective clinical trial study using the optique rigid to evaluate and insert the tracheal balloon under suspension laryngeal endoscopy to dilatation and maintain the fracture of laryngeal trauma. Using the balloon of the No.5 endotracheal tube like laryngeal stent during 10 to 14 days. Results: 54 laryngeal trauma cases (92.3% male) have been treated by endoscopic surgery at Ear-Nose-Throat (ENT) Department at Cho Ray Hospital in Ho Chi Minh City from May 2015 to August 2016. Closed trauma is more frequent than open trauma. Hoarseness, dyspnea, and subcutaneous emphysema are mostly seen. Endoscopy, CT-scan help to diagnose the trauma location with 85.1% success percent. Conclusions: The method balloon pharyngoplasty under suspension laryngeal endoscopy to management of laryngotracheal trauma is non-invasive, not difficult and technique can ensure a successful outcome.